Influence of the injection current sweep rate on the polarization switching of vertical-cavity surface-emitting lasers - Masoller, C. (2006)
We study the polarization switching of vertical-cavity surface-emitting lasers based on simulations of the spin-flip model. We show that the switching point depends on the ramp signal used to scan the injected current. Fast current ramps enlarge the hysteresis region since the switching point moves to high pump values for increasing injection and to low pump values for decreasing injection. The delay of the bifurcation follows a power law with the slope of the current ramp.